Evaluating chemical venous thromboembolism prophylaxis in trauma patients at a single Australian center - Natalie Quarmby; Minh Tu Vo; Sean Weng Chan (Journal of Trauma and Injury)
Purpose Trauma patients are at an elevated risk of developing venous thromboembolism (VTE), with the subsequent mortality in patients requiring intensive care unit admission ranging from 25% to 38%. There remains significant variability in clinical practice related to VTE prophylaxis in trauma patients due to the frequent presence of contraindications impacting the timing and consistency of application. This study aimed to assess the effectiveness of the current practice of chemical VTE prophylaxis in trauma patients at a single Australian center. Methods A prospective review was conducted on patients admitted to the ACT Trauma Service (Canberra, Australia) from July to November 2022. The included patients were 18 years or older, without a direct contraindication to anticoagulation, who received chemical VTE prophylaxis with low-molecular-weight heparin (enoxaparin) for at least three doses and underwent subsequent testing of anti-factor Xa (aFXa) levels. Results During the study period, 187 patients were admitted, of whom 63 were included in the study. Of these, 47 patients achieved therapeutic levels of anticoagulation as determined by their aFXa levels, while 16 were subtherapeutic. The only statistically significant difference between the two groups was in weight, with patients in the subtherapeutic group weighing an average of 91.9 kg compared to 79.1 kg in the therapeutic group (P<0.05). Conclusions A fixed-dose enoxaparin regimen was utilized, with limited individualization based on patient factors, such as injuries, comorbidities, and other biological factors. Sixteen patients (25%) had subtherapeutic VTE prophylaxis, as measured by aFXa levels. Higher weight was significantly correlated with inadequate VTE prophylaxis dosing. While age, sex, and smoking status might play important roles in clinical decision-making, weight-based dosing of low-molecular-weight heparin may be more effective in achieving adequate VTE prophylaxis.